Symmetric private information retrieval supported by quantum-secure key-exchange network - Wang, Shuang (Light, science & applications, 2022)
Quantum key distribution provides a provably secure way for private key distribution, which enables the practical implementation of information retrieval that preserves both the user privacy and database security.